Filosofi, asas, ajaran, teori hukum pertanahan, dan agraria / Herman Soesangobeng ; editor, Tjahjo Arianto. - HERMAN SOESANGOBENG; Tjahjo Arianto. (: STPN Press, 2012)
xxvi, 341 hlm. : ilus. ; 23 cm (2 eks)